AMIC sets sights on Green Aviation - Universiti Putra Malaysia, Bahagian Komunikasi Korporat (2011)
The Aerospace Malaysian Innovation Centre (AMIC), a consortium-led project spearheaded by European Aeronautics Defence and Space Company (EADS), Rolls Royce, Composite Technology Research Malaysia (CTRM) and the Government of Malaysia convened its first board meeting on Monday, 14 Nov 2011, setting research priorities for upcoming projects. Science Advisor to Prime Minister Prof. Emeritus Datuk Dr Zakri Abdul Hamid and Chief Technical Officer of EADS Dr Jean Botti are the joint chairmen for the Board of directors.